2001
DOI: 10.1103/physrevlett.86.4431
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and Extreme Spin Squeezing

Abstract: For any mean value of a Cartesian component of a spin vector we identify the smallest possible uncertainty in any of the orthogonal components. The corresponding states are optimal for spectroscopy and atomic clocks. We show that the results for different spin J can be used to identify entanglement and to quantify the depth of entanglement in systems with many particles. With the procedure developed in this Letter, collective spin measurements on an ensemble of particles can be used as an experimental proof of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
595
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(609 citation statements)
references
References 21 publications
13
595
0
1
Order By: Relevance
“…While prior to this work a negative Wigner function had not been attained for atomic ensembles, in the optical domain, a negativevalued Wigner function has very recently been measured for states with up to 110 microwave photons [18]. Another entanglement measure is the entanglement depth [19], i.e. the minimum number of atoms that are demonstrably, but possibly weakly, entangled with one another.…”
mentioning
confidence: 99%
“…While prior to this work a negative Wigner function had not been attained for atomic ensembles, in the optical domain, a negativevalued Wigner function has very recently been measured for states with up to 110 microwave photons [18]. Another entanglement measure is the entanglement depth [19], i.e. the minimum number of atoms that are demonstrably, but possibly weakly, entangled with one another.…”
mentioning
confidence: 99%
“…In spin squeezing, the uncertainty of one component of the (total) spin is reduced below the uncertainty limit at the expense of increased uncertainty in an orthogonal component 100 . Interestingly, it was shown theoretically that sufficiently strong spin squeezing implies entanglement in the spin bath 101 . As another example, although harder to achieve with current techniques, proposals exist for coherent exchange of a qubit state between the quantum dot electron spin and a collective degree of freedom of the nuclear spin bath 15 .…”
Section: Future Directions and Other Materialsmentioning
confidence: 99%
“…We found that for values higher than N η = 10 4 we can achieve better results for the squeezing parameter improving further as the value of the cooperativity gets increased, a behavior we observe also in simulations with different N . Additionally, we compared the results of the optimized pulses with the adiabatic protocol of Sørensen and Mølmer [16] which achieves optimal squeezing for long time-scales and high cooperativities. In Fig.…”
mentioning
confidence: 99%
“…The second protocol, proposed by Sørensen and Mølmer, is based on adiabatic evolution to steer a system into maximally squeezed states squeezing the variance ∆ 2 J x under the constraint that J z is nonzero. [16].…”
mentioning
confidence: 99%